The Prevalence of Integron Classes Genes Among A. Baumannii Isolates - Mahmood, Suhad S (Iraqi Journal of Science, 2022)
Acinetobacter baumannii has been recently classified as a major threat to public health because it has resistant to almost all antibiotics and there are many reasons that are responsible for conferring this feature to A. baumannii. One of these reasons is integrons so in this study we show the role of the integrons in providing resistance to some antibiotics. A number of 60 isolates were collected from different clinical sources of patients who were admitted to Baghdad hospitals and all isolates were diagnosed using biochemical tests and confirmed using  Chrom-ager culture media, and Vitek 2 compact system. The antibiotic susceptibility test was determined during this study using Kirby-Bauer method and the results of susceptibility demonstrate that these bacteria are responsible for providing resistance to Amikacin, Trimethoprim, Piperacillin, Cefepime, Tetracycline, Ampicillin-sulbactam, Imipenem, and levofloxacin. All isolates show high resistance to trimethoprim and low resistance to tetracycline. The presence of integrons in A. baumannii was detected using conventional polymerase chain reactions. The results showed integron class I was found in all 60 isolates with a percentage (100%) while integron class II was found only in 7 isolates with a percentage  (11.6%) and the results of detection showed integron class III are not found in the examined isolates. This study conclude that all  A. baumnnii isolates had the strongest resistance to various antibiotics, and the class 1 integron appeared to be the most dominant class among class II and III .